Multicultural Education Theory according to Martin J. Beck Matustik in the Perspective of Islamic Religious Education (PAI) - Khoiri Khoiri; St Wardah Hanafie Das (PT. Anagata Sembagi Education, 2024)
Multicultural education emphasizes respect for cultural, religious, and ethnic diversity, which becomes very relevant in Indonesia as a country with rich plurality. In this context, the application of multicultural education theory, especially in Islamic Religious Education (PAI), has a strategic role in creating a more inclusive and harmonious society. This article aims to examine the theory of multicultural education according to Martin J. Beck Matustik, which consists of three main pillars: (1) recognition of diversity, (2) dialogue between cultures and religions, and (3) social justice. These pillars are very relevant to be integrated in the PAI curriculum, so as to form a generation that is not only intelligent in religious aspects, but also open, tolerant, and respectful of differences. The methodology used in this research is a qualitative approach with descriptive analysis, through a literature review that includes literature related to multicultural theory and its application in PAI. Data were also taken from PAI curriculum documents in Indonesia to explore the potential integration of multicultural values. The results showed that the application of multicultural education principles in PAI can encourage the creation of a more just and peaceful society, by producing individuals who are able to interact constructively and appreciate differences. Thus, Islamic religious education that promotes multicultural values is expected to be a solution to face the challenges of globalization and strengthen a more harmonious common life in Indonesia